Pelatihan Pelvic Rocking Exercise Sebagai Upaya Pendampingan Penanganan Nyeri Punggung Pada Ibu Hamil Di Posyandu Kemuning Sondakan Laweyan Surakarta - Darah Ifalahma; Ana Yuliana; Anik Sulistiyanti; Adisty Amalya Putri Handayani (Jurnal Pengabdian Bidang Kesehatan, 2024)
Posyandu Kemuning is one of the posyandu in Sondakan Laweyan Subdistrict, Surakarta and is included in the UPT Puskesmas Pajang Surakarta area. Posyandu Kemuning has 20 health cadres. Like posyandu in general, the monthly activity at Posyandu Kemuning is checking babies and toddlers and pregnant women. Data for April 2024 showed that the number of pregnant women was 23, with details of 6 pregnant women in the first trimester, 7 pregnant women in the second trimester and 10 pregnant women in the third trimester. Of the 10 pregnant women in the third trimester, all experienced complaints of back pain and had not received assistance from cadres. The negative impact of back pain is interference in daily physical activities. Back pain that is not treated properly in pregnant women can cause poor quality of life for the mother. The priority problem found at Posyandu Kemuning was the limited knowledge and skills of cadres in assisting pregnant women with back pain. Cadres do not understand about back pain during pregnancy and do not have the complementary Pelvic Rocking Exercise skills to treat back pain during pregnancy. The focus of this community service activity is to provide training to cadres on Pelvic Rocking Exercise as an effort to assist in handling back pain for pregnant women at Posyandu Kemuning Sondakan Laweyan Surakarta. The method used consists of 6 stages, namely Preparation, Apperception, Training, Post-training assistance, Evaluation and Termination of activity results. The results of the activity were that cadres' knowledge in the good category before and after counseling increased by 25%, most of the cadres' skills regarding Pelvic Rocking Exercise were in the good category, namely 13 cadres (65%). Cadre assistance activities in treating back pain in pregnant women at Posyandu Kemuning Sondakan Laweyan Surakarta have gone well. Cadres are committed to carrying out and implementing the results of activities in assisting pregnant women.